Capital controls checkup: Cases, customs, consequences - Stefan Goldbach; Volker Nitsch (Deutsche Bundesbank, 2020)
This paper examines the effect of administrative restrictions on cross-border capital transactions. Using highly disaggregated data from the German balance of payments statistics for the period from 1999 through 2017, we document several stylized facts about the effectiveness of such capital control policies introduced by other countries. Capital controls are associated with economically and statistically significant declines in capital flows; they affect bilateral financial relationships along both the extensive and the intensive margin. Capital controls have also been effective in reducing capital flows within the European Union.
Keywords: F32; F36; F38; 330; restriction; capital flow; transaction